Intraluminal pressure, transmucosal potential difference, and pH studies in the oesophagus of patients before and after Collis repair of a hiatal hernia. Issue 3 (May 1973) - Habibulla, K. S.; Collis, J. Leigh
Abstract : Intraluminal pressure, transmucosal potential difference, and endo-oesophageal pH measurements were studied in patients with hiatal hernia—before and after a hiatal repair. The operation employed is the Collis (1968) repair for uncomplicated hiatal hernia and does not refer to gastroplasty as recommended for peptic stricture (Collis, 1961). Postoperative studies show that the repair approximates the inferior oesophageal sphincter to the hiatus with the production of a single band of raised pressure at the lower end of the oesophagus. This band is similar to that seen in normal subjects and its appearance was associated with cure of the symptoms, abolition of the gastro-oesophageal reflux, and improvement in the function of the inferior oesophageal sphincter and the musculature of the body of the oesophagus. Certain physiological implications of this study are discussed.